Heutagogy learning during pandemic Covid-19: descriptive analysis among senior high school students in Indonesia / Endang Fitriyah Mannan, Shamila Mohamed Shuhidan and Mohamad Noorman Masrek - Mannan, Endang Fitriyah; Mohamed Shuhidan, Shamila; Masrek, Mohamad Noorman (Faculty of Information Management, 2022)
The Covid-19 pandemic has caused sudden disruptions, including learning in schools. A new approach, heutagogy, in learning is expected to be a solution. This study aims to conduct a descriptive analysis of heutagogy learning during the covid 19 pandemic among senior high school students in Indonesia. The research approach is quantitative. The questionnaire was distributed online and has been filled out by 450 respondents. The results show that the highest mean in the learner agency dimension is attitude, the capability dimension is communication, the reflection dimension is know-in-action, and the non-linear design is the ability to handle ambiguity